Basketball shooting performance is maximized by individual-specific optimal release strategies - Slegers, N. (International Journal of Performance Analysis in Sport, 2022)
This study investigated the relationship between optimal basketball release angles and individual release distributions and whether individuals seek their optimal or minimum velocity release strategy. Sixteen male basketball players (height 183 ± 9 cm, age 22.6 ± 7 years) were recorded shooting 75 three-point shots. Ball release angle and velocity estimates were used in a nonparametric kernel density estimator (KDE) to identify individual-specific release distributions and optimal release angles. Optimal releases varied among individuals and were 4.3 ± 2.1° higher than minimum velocity releases. Mean release angles were 3.9° higher than the minimum velocity angle (p < 0.001) and only 0.4° below the optimal (p = 0.5). Participants skewed their probability density function (PDF) peaks 0.24° towards the optimal (p = 0.044) further indicating participants seek optimal rather than minimum velocity releases. Individual-specific optimal release angles were strongly correlated with their PDF covariance (r = 0.78, p < 0.001) and weakly correlated to the principal axis aspect ratio (r = -0.40, p = 0.137). These findings illustrate that optimal releases varied among participants and performance may be maximised by each athlete matching their release strategy to their PDF characteristics rather than matching a predetermined optimal release angle.